EFFECT OF TREATED SEWAGE EFFLUENT IRRIGATION ON P DYNAMICS IN SOIL - R. P. RAJIMOL; M. HEBBARA; M.V. MANJUNATHA. (The Bioscan, 2020)
A study emphasizing the effect of constructed wetland treatment of domestic sewage effluent on its quality and subsequent effect of irrigation on soil phosphorus dynamics both spatially and temporally with tomato as a test crop was carried out at the Main Agricultural Research Station, Dharwad, Karnataka during January to May, 2014. The effluent after passing through the constructed wetland improved its quality which was reflected by the reduction in pH, EC, BOD, COD, TSS, TN, ON and TP compared to the untreated sewage effluent (USE). The mean reduction in TSS, BOD and COD in the treated effluent over USE was 42, 54 and 39 per cent, respectively. Among the various soil P fractions analyzed, Ca-P was the most dominant active inorganic P fraction whereas the least dominant was saloid P at 0-20 and 20-40 cm depth throughout the experimental course. Similar to other fractions sewage irrigated plots recorded highest organic P. The relative trend of abundance of P fractions was in the order of organic -P> Ca-P> Al-P> Fe-P> occluded -P> reductant soluble P> saloid-P.